Results obtained from 105 successive patients admitted with severe ischemia threatening limb loss - Rudnitzky, Omar; Davezac, Víctor; Blanco, Raúl; Gordillo, Felipe; Folle, Enrique; Monti, José; Lombardi, Gerardo; Font, Francisco; Wins, Richard; Chevalier, Nelmar; Boschiero, Ana; Ribeiro, Gustavo; et al. (Cirugía del Uruguay, 1993)
The article deals with a prospective study assesing the results from 105 patients who were successive, with no previous selection, with chronic critical ischemia, running an immediate high risk of loosing the foot support.